Beyond Belief: Surviving the Revocation of the Edict of Nantes in France - Wilson, Christie Sample (Lexington Books, 2011)
Beyond Belief: Surviving the Revocation of the Edict of Nantes examines the degree to which the Revocation of the Edict of Nantes was a negotiated event — which called upon individuals and communities to find ways to coexist without abandoning the faith of their fathers — and at the same time illuminates the limits of the absolutist state whose policies were not always supported by officials on the regional and local level.